Evaluate the performance of certification competence vocational students through certification institute profesi-p1 program computer engineering expertise and tissues at south sumatra - Dian Nurdianto; Syarwani Ahmad; Mulyadi Mulyadi (Indonesian Institute for Counseling, Education and Therapy (IICET), 2021)
This study attempts to evaluate the performance of certification competence described vocational students through certification institute profesi-p1 program computer engineering expertise and tissues at south sumatra .This study in a qualitative descriptive with those cases .Data collection techniques used in this research was the questionnaire , interview , and use a method of triangulation dokumentasi.teknik data analysis and collect information or data from various sources to check the truth of the data .The results of the study conclude that so it can be seen that the purpose of the vocational school vocational certification in 1 penukal with objectives set the national profession certificates show category in accordance with the percentage of 75 % Sedangkan to state 1 indralaya south objectives set the national profession certificatesshow category in accordance with the percentage of only 72 %.